Management Of Lawang Ombo As A Tourism Destination Based On Historic Buildings (Comparation Before And During The Pandemic) - Nataly Dinda Savira; Eko Sugiarto (International Journal Of Tourism, 2023)
This study was conducted in Lawang Ombo, located in Lasem District, Rembang Regency, Central Jawa. Lawang Ombo is a residential building built by Liem King Siok. Lawang Ombo has previously been used as a place for opium smuggling, which is a profitable illegal trade. The descriptive-comparative method was used in this study to compare the condition of Lawang Ombo as a tourism destination based on historical buildings before and during the pandemic and its management. The results of this study indicate that before the Covid-19 pandemic, Lawang Ombo was the location for various cultural performances. Visitors come from various cities in Central Java. During the pandemic, all cultural activities at Lawang Ombo were stopped. Very few visitors came and only came from Rembang. This makes no income from tourists for management costs. The next impact is that this building looks dirty and less maintenance. Based on the results of this study, it can be concluded that historic building-based tourism destinations that rely on income from tourists, especially through cultural performances, need to have income from other sources for management costs so that when performances are not possible to be held, the management of these historic buildings can continue. Keywords: Tourism Destination; Historical Building; Lawang Ombo; Pandemic.